IMPLEMENTASI PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI SEKOLAH - Cepi Riyana (MAJALAH ILMIAH PEMBELAJARAN, 2007)
AbstractInformation and Communication Technology (ICT) is a new subject in schools. Therefore, it needs further analysis in the implementation at schools especially in its learning aspects. This article is based on a research in the procedure and factors that will effect the implementation of ICT subject in schools. The results shows two main procedure applied in ICT learning in Senior High School are general and specific procedures. General procedures consist of Planning, Implementation and Evaluation. Specific procedure consist of learning preparation: understanding the standard operation procedure as a requirement in works safety, understanding the ethics in using ICT and entering behavior level. In the learning process, consist of understanding the operating system, peripheral setting, Data management for increasing productivity and software development. In the evaluation process, consist of pencil and paper test, performance test, product evaluation in portfolio. Some factors that affect the ICT implementation are internal factors: teacher (related to achievement motivation and ICT literacy), students, facilities, and external factors: support from schools, society and government.